2011
DOI: 10.4055/cios.2011.3.1.16
|View full text |Cite
|
Sign up to set email alerts
|

Subsidence and Nonunion after Anterior Cervical Interbody Fusion Using a Stand-Alone Polyetheretherketone (PEEK) Cage

Abstract: BackgroundThe purposes of the present study are to evaluate the subsidence and nonunion that occurred after anterior cervical discectomy and fusion using a stand-alone intervertebral cage and to analyze the risk factors for the complications.MethodsThirty-eight patients (47 segments) who underwent anterior cervical fusion using a stand-alone polyetheretherketone (PEEK) cage and an autologous cancellous iliac bone graft from June 2003 to August 2008 were enrolled in this study. The anterior and posterior segmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
126
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(130 citation statements)
references
References 27 publications
4
126
0
Order By: Relevance
“…519,520 Because of its low compatibility for bone tissue, however, PEEK has been associated with the problem of insufficient bone union when used in implants that are directly exposed to bone, such as interbody fusion cages. 521524 MWCNTs have been reported by many research teams, including ours, to possess bone induction potential. 58,62,63,67,213,215,216,218,525,526 If conjugation with MWCNTs further improves the mechanical characteristics of PEEK and also induces osteogenesis, then MWCNT/PEEK composite will become an ideal interbody fusion material (Figure 13).…”
Section: Discussion and Perspectivementioning
confidence: 76%
“…519,520 Because of its low compatibility for bone tissue, however, PEEK has been associated with the problem of insufficient bone union when used in implants that are directly exposed to bone, such as interbody fusion cages. 521524 MWCNTs have been reported by many research teams, including ours, to possess bone induction potential. 58,62,63,67,213,215,216,218,525,526 If conjugation with MWCNTs further improves the mechanical characteristics of PEEK and also induces osteogenesis, then MWCNT/PEEK composite will become an ideal interbody fusion material (Figure 13).…”
Section: Discussion and Perspectivementioning
confidence: 76%
“…The design and development of a suitable fusion cage to replace a degenerated disc are currently being performed. 5,7 A possible solution for many of these problems may be a bioabsorbable cage. PLA is currently the most popular material that is used to make bioabsorbable cages, and these cages can be designed with similar stiffness to a human bone to reduce stress shielding.…”
mentioning
confidence: 99%
“…Subsidence and nonunion have several risk factors 2,4,7,24,25 . As for examples, wrong surgical techniques such as over distraction, endplate damage, and inadequate preparation of endplate.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Park et al 12 , there were 22.6% subsidence and 9.7% nonunion. Yang et al 25 reported in their study of ACDF with stand-alone case filled with iliac crest bone graft that25.5% subsidence and 14.9% nonunion. In a similar study by Bartels et al 2 in ACDF using a stand-alone cage packed with local autologous bone graft from the adjacent vertebrae found, 29.2% subsidence and 4.3% nonunion.…”
Section: Introductionmentioning
confidence: 99%